2022
DOI: 10.1155/2022/5169548
|View full text |Cite|
|
Sign up to set email alerts
|

Load Test Analysis of a Long-Span Prestressed Nano-Concrete Highway Bridge

Abstract: In order to solve the problem of vehicle-bridge coupling vibration of a continuous semisteel bridge, the main bridge type of long-span prestressed concrete girder bridge, the author proposes a bridge safety test system based on the dynamic and static load test. The system combines the change of stress and deflection with the vibration amplitude of the bridge body, and using the modeling assistant in large-scale finite element software MIDAS/CIVIL, a three-dimensional finite element real bridge model is establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The constant loads are determined accountig the actual thickness and materials of bridge road deck layers according to the survey results. Static calculation of the span section's main beams is made by method of eccentric compression according to the methods of structural mechanics [1,[16][17][18]22] to determine TIC of vehicles A-15, NK-100 and pedestrian load for the outermost beam B1 and central beam B4 of the span structure in the cross-section of the bridge.…”
Section: Methodsmentioning
confidence: 99%
“…The constant loads are determined accountig the actual thickness and materials of bridge road deck layers according to the survey results. Static calculation of the span section's main beams is made by method of eccentric compression according to the methods of structural mechanics [1,[16][17][18]22] to determine TIC of vehicles A-15, NK-100 and pedestrian load for the outermost beam B1 and central beam B4 of the span structure in the cross-section of the bridge.…”
Section: Methodsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%